Russian Orthodoxy resurgent : faith and power in the new Russia - Garrard, John Gordon (Princeton University Press, 2008)
Russian Orthodoxy Resurgent is the first book to fully explore the expansive and ill-understood role that Russia's ancient Christian faith has played in the fall of Soviet Communism and in the rise of Russian nationalism today. John and Carol Garrard tell the story of how the Orthodox Church's moral weight helped defeat the 1991 coup against Gorbachev launched by Communist Party hardliners. The Soviet Union disintegrated, leaving Russians searching for a usable past. The Garrards reveal how Patriarch Aleksy II--a former KGB officer and the man behind the church's successful defeat of the coup-